Adopting and Adapting Hermeneutic Method Within Translation Studies - Vaňková, Ingrida (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The present study focuses on the application of the hermeneutic method within translation process. The examination of the issue draws on the already established concepts of translational hermeneutics, which consider this method as a part of the initial phase of the translation activity. However, the study presents the approach according to which hermeneuticactivity is present throughout whole translation process. The author thus examines deployment of Ricoeur’s hermeneutic concept of interpretation and understanding of the complex translation activity. Finally, a new hermeneutic-pragmalinguistic conceptualization method is introduced applying the hermeneutic approach within the complex translation process. It is noted that on a semantic level the person who pronounces the word I, which is associated with a specific name, forms personal identity. At the pragmatic level, the meaning of the word I become contextually dependent on the discourse in which it is constantly formed. On the borderline between semantics and pragmatics, a person becomes a reflexive Self, capable of hermeneutical activity of understanding. The author focuses on Ricoeur's research, which defines language as an objective system and / or code and discourse. He also argues that language as a code is collective in that it exists as a set of parallel rules (synchronous system) and is anonymous in the sense that it is not theresult of any intention. The language is not conscious in terms of structural or cultural unconsciousness. The author focuses on the stages of hermeneutic activity. This indicates that the first stepreveals the essence of interpretation as an important part of the hermeneutical method, which is a dynamic process that includes a non-methodological moment of understanding and a methodological moment of explanation. Characterizes the second stage of hermeneutic activity it is the stage of configuration. That is, the stage of conceptualizing meaning in language. The third stage, that is, the stage of refiguration, is a complete understanding of the discourse and its interpretation. Hermeneutic activity is fully realized in reading, which represents the space between pragmatics and semantic structure. This phenomenon is described as the stage where a person operates with all their knowledge, pragmatic language and experience, not yet structured to solve one particular cognitive-reflexive task. With regard to the thematic and non-thematic cognitive abilities of each person, the translator, as a professional user of at least two languages, has a cognitive-reflexive knowledge in which at least two language cultures interrelate and intersect. It is vaccinated that, at the interlingual and interlingual levels of hermeneutic activity (in interpretation and understanding), an individual not only uses language but also changes andtransforms it.